2019
DOI: 10.1101/683565
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large-scale dissection suggests that ultraconserved elements are dispensable for mouse embryonic stem cell survival and fitness

Abstract: Ultraconserved elements (UCEs) are genomic regions that are highly conserved among vertebrates and are under extreme purifying selection. Despite this extreme conservation, the biological importance of UCEs has remained elusive thus far. Here, we investigate the relevance of 93 UCEs for survival and fitness of mouse embryonic stem cells (mESCs) utilizing CRISPR/Cas9 technology. Surprisingly, systematic analyses of deletion clones revealed no measurable effects on mESC viability, proliferation or morphology.Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Because of their extraordinary sequence conservation, ultraconserved elements were initially assumed to be essential for life 12 . However, deletion of many ultraconserved enhancers has no effects on mouse organismal or cell viability [62][63][64][65] . Although poison exons are similar to enhancers with respect to their gene regulatory activities, we found that many poison exons exert robust effects on cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their extraordinary sequence conservation, ultraconserved elements were initially assumed to be essential for life 12 . However, deletion of many ultraconserved enhancers has no effects on mouse organismal or cell viability [62][63][64][65] . Although poison exons are similar to enhancers with respect to their gene regulatory activities, we found that many poison exons exert robust effects on cell viability.…”
Section: Discussionmentioning
confidence: 99%